Technological and devices modeling of complementary JFETs over a wide temperature range. (November 2020) - Drozdov, D.G.; Prokopenko, N.N.; Savchenko, E.M.; Dukanov, P.A.; Rodin, V.G.; Grushin, A.I.
Abstract: The article presents the results of process and device modeling results of complementary junction field-effect transistors (JFET). The models necessary for calculating the JFET in the temperature range down to cryogenic were described: the Klaassen model of the carriers mobility (Phillips company model) and Shockley-Read-Hall recombination model, taking into account the doping dependence, Lackner's model of avalanche multiplication, Fermi-Dirac statistics, Slotboom model, designed to describe the dependence of the band gap on the doping concentration. These models take into account the effect of temperature. We have described in detail the model of incomplete ionization of an impurity, which determines the concentration of charge carriers at cryogenic temperatures. The TCAD-based JFET self-heating effect is simulated using a simplified model that significantly reduces the calculation time compared to the thermodynamic model. Studies on the selection of an algorithm for calculating a system of differential equations in the temperature region are carried out. It is shown that the SLIP90 algorithm provides calculations in the entire temperature range down to T = 25 K. The article shows that modification of the design can significantly affect the choice of calculation algorithm. The dependences of the main JFET parameters are analyzed taking into account the selected models on temperature and constructive and technological solutions are proposed to reduce the influence of ultra-low temperatures on the parameters of complementary JFETs.The research results showed that reducing the cut-off voltage reduces the influence of temperature on the shorted-gate drain current JFET in the temperature range. At the same time, n-channel transistors have advantages in terms of a smaller change in parameters over the temperature range down to the temperatures at which the "freezing out" of the impurity charge carriers begins. Several types of transistor topologies were simulated in the temperature range, which showed that the value of the shorted-gate drain current increases linearly with the number of gates. However, there are differences in the dependence of the main parameters in the temperature range depending on the design of the layers of complementary JFETs. Using the emitter region as the top gate weakly affects the parameters of the n-channel JFET in the case of the formation of complementary JFETs in the microwave complementary bipolar technological process, and for the p-channel JFET the temperature stability of the parameters deteriorates. For the p-channel transistor with a gate based on the base region, the temperature stability over the range Δ T = 150–330 K of the shorted-gate drain current is higher than for the transistor with a gate based on the emitter. For the n-channel transistor, the dependence is inverse. Over the range Δ T = 150–77 K, the dependence of the parameters of the transistors for two structures does not differ. In principle, the results show that the change in the ambient temperature has a greater effect on the p-channel transistor than on the n-channel. Graphical abstract: Relative time of calculation for n-JFET ( U GS = 0 V, U DS = 5 V) with different solvers and temperatures. Image 1 Highlights: TCAD. Complementary junction field-effect transistors. Cryogenic temperature. Model of incomplete ionization of the impurity. Algorithms for calculating a system of differential equations.